2011
DOI: 10.1111/j.1365-2893.2010.01328.x
|View full text |Cite
|
Sign up to set email alerts
|

The hepatitis C self‐management programme: a randomized controlled trial

Abstract: Chronic hepatitis C (HCV) infection afflicts millions of people worldwide. While antiviral treatments are effective for some patients, many either cannot or choose not to receive antiviral treatment. Education about behavioural changes like alcohol avoidance and symptom management, in contrast, is universally recommended, particularly in HCV-infected persons from disadvantaged groups where liver risk factors are most prevalent. Self-management interventions are one option for fostering improved HCV knowledge a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 59 publications
5
29
0
Order By: Relevance
“…Self‐efficacy beliefs are important targets for clinical intervention, given that they can be enhanced, resulting in improved patient self‐management of chronic illness, including chronic hepatitis C [35,36]. However, self‐efficacy requires measurement precision specific to the [1] behaviour being studied (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self‐efficacy beliefs are important targets for clinical intervention, given that they can be enhanced, resulting in improved patient self‐management of chronic illness, including chronic hepatitis C [35,36]. However, self‐efficacy requires measurement precision specific to the [1] behaviour being studied (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the importance of self‐efficacy to medication adherence in other medical regimens, there is limited research in the HCV literature that examines self‐efficacy beliefs, and no studies were identified that examined these beliefs during antiviral treatment [35,36]. A self‐efficacy measure was included in the NIH‐funded study, Viral Resistance to Antiviral Therapy of Chronic Hepatitis C (VIRAHEP‐C) study.…”
Section: Introductionmentioning
confidence: 99%
“…Given that patients experience preexisting clusters of somatic/neurovegetative symptoms in the early weeks of treatment (e.g., fatigue, insomnia, pain, headache) that lead to reduced HrQOL and worsening depression later in treatment, multi-component psychological interventions that treat multiple concurrent symptoms and improve overall coping skills may be highly beneficial. Empirically-proven psychological treatments for other disease symptoms and treatment side effects exist and can be adapted for HCV treatment (Andersen et al, 2004; Antoni, Ironson, & Schneiderman, 2007; Given et al, 2004; Groessl et al, 2011; Safren et al, 2009). …”
Section: Psychological and Behavioral Intervention Research In Hcv Psmentioning
confidence: 99%
“…Adherence to standardized HIV care and treatment regimens is essential to achieve optimal health outcomes. Nonetheless, public health officials estimate only one fourth of Americans who are living with HIV are successfully managing virus-related sequelae (Hall et al, 2013), which is disheartening given that self-management of other chronic conditions has been associated with better health outcomes (Barlow, Wright, Sheasby, Turner, & Hainsworth, 2002;Groessl et al, 2011;Lorig, Ritter, Laurent, & Plant, 2006;Ory et al, 2013).…”
mentioning
confidence: 99%